O przekładzie tytułu (na przykładzie prozy słoweńskiej) - Gawlak, Monika (Przekłady Literatur Słowiańskich, 2015)
On the Translation of a Title (basing on the Slovenian prose) The article concerns the issue of the interpreter’s freedom concerning translations of the titles of prose works. The matter seems important not only because of the necessity of reserving the title’s essential functions (identification, information, pragmatics), not only because of the need of a complex analysis of the original title — work relationship, but also because of the ‘ambassadorial’ role of — this title in the secondary cultural space. Attention was drawn to the praxis of giving the interpreted collections of short stories (Terra Incognita, Noc w Lublanie) titles already existing in the initial culture and given to other publications. It is malpractice and misleading to a secondary reader. Also, the titles with a remaining foreign dominant element (Čefurzy raus!) and titles significantly different from the original titles (Słońce w dolinie, Białe czereśnie, Pies) were discussed. The space of freedom and the opportunity of a creative attitude appears especially in cases of titles containing a the foreign element, those which do not evoke almost any associations to the secondary reader. In these cases, the most appropriate practice seems to be deleting the original title and giving a new one, one dependent on the work’s interpretation or containing its important subject or topos. Then, the interpreter’s freedom is limited due to the nature of pragmatic and moral imperatives. In choosing the new title, the interpreter should be guided principally by the desire to ensure that the work reaches as many readers in the new cultural space as possible. Key words: title translation, freedom of the interpreter, translating Slovenian prose, foreignness in translation